Antibacterial Activity of Tamarind Leaf-Based Shampoo Against Staphylococcus aureus and Pseudomonas aeruginosa, Candida albicans, and Malesezia globose - Sari, Wahyu Eka; Sadri, Hidayatus; Hasanah, Lailatul; Yona, Safetri; Triyuliani, Ririn; Maghfirah, Aura; Frengki, Frengki; Riandi, Lian Varis; Riady, Ginta (Jurnal Medika Veterinaria, 2023)
Skin and feather diseases are common in cats. The main causative agents of these diseases are bacteria and fungi, including Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans, and Malassezia globosa fungi which are one of the fungi that play a role in the formation of dandruff. Preventive measures that can be carried out are grooming or bathing cats using special shampoos. The use of natural-based shampoos is an alternative to reduce the side effects of using chemical-based shampoos. Like herbal shampoo from tamarind leaf extract. The samples used in the study were tamarind leaves and isolates of S. aureus and P. aeruginosa, C. albicans and M. globosa. This research used completely randomized design (CRD) model with three treatment groups (2% and 20% for extract, tamarind leaf extract shampoo) for antibacterial test. Positive controls consisted of vancomycin 30 mg for S. aureus, and gentamicin 10 mg for P. aeruginosa, and distilled water as negative control. For antifungal test, there were three different concentrations (16%, 8%, and 4%), tamarind leaf extract shampoo, one positive control (zinc pyrithione 1%) and one negative control (distilled water) with two replications. Data was analyzed by measuring the inhibition zone formed. The results of the inhibition zone on S. aureus were 6.03 mm (2%) and 13.48 mm (20%), and for tamarind leaf extract shampoo was 9.54 mm, categorized as weak. For P. aeruginosa, the inhibition zone was 6.61 for 2%, and 19.78 for 20% (categorized as strong), tamarind leaf extract shampoo was 10.23 mm (weak category. For C. albicans, inhibition zone formed at a concentration of 4% was 6 mm, 8% was 6 mm, 16% was 6 mm, and tamarind leaf extract shampoo was 6 mm, (weak category). For M. globosa at a concentration of 4% was 0 mm, 8% was 6 mm, 16% was 6 mm, and tamarind leaf extract shampoo was 12.32 mm (strong category). It can be concluded that the ethanolic extract of tamarind leaf had inhibition activity on the growth of S. aureus, P. aeruginosa, C. albicans, and M. globosa.